Succession of generations is still the general paradigm for scyphozoan life cycles - Morandini, André C.; Schiariti, Agustín; Stampar, Sergio N. [UNESP]; Maronna, Maximiliano M.; Straehler-Pohl, Ilka; Marques, Antonio C. (Bulletin of Marine Science, 2016)
A recent study proposed an unorthodox view of the long-known metagenetic life cycle of scyphozoan jellyfish. We argue that misinterpretations and imprecise information generated a misleading view of such life cycle patterns. In favor of our reasoning, we present the historical understanding of metagenesis, and contend that it can still be used as a shared general life cycle pattern for Scyphozoa, as well as for other medusozoans.